Keterlibatan Warga Negara (Civic Engagement) dalam Penguatan Karakter Peduli Lingkungan - Setiawan Gusmadi (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2018)
This paper aims to explore deeply about civic engagement in strengthening environmental cares. Civic engagement refers to the way citizens participate in the life of a community to improve the condition of others or to help shape the future of society. The writing of this paper is supported by literature studies and relevant research journals in the form of national journals and international journals. Civic engagement is expected to strengthen the character of environmental care clean, healthy, comfortable, and cultured environment. Movement to improve the environment of a more effective society must be supported in terms of education that develops responsible, creative and knowledgeable society. Civic engagement becomes important to contribute in a community that moves to manage, preserve and preserve the environment such as the development strategy of the Mangrove Center Foundation.